2003
DOI: 10.1073/pnas.0337625100
|View full text |Cite
|
Sign up to set email alerts
|

Expression and mechanistic analysis of a germacradienol synthase from Streptomyces coelicolor implicated in geosmin biosynthesis

Abstract: The PCR has been used to amplify a 2,181-bp ORF from Streptomyces coelicolor A3(2), designated SC9B1.20 ‫؍(‬ SCO6073), encoding a protein of 726 amino acids and showing significant sequence similarity at the deduced amino acid level in both the N-terminal and C-terminal halves to the known sesquiterpene synthase pentalenene synthase. The full-length recombinant protein was expressed at high levels in Escherichia coli and shown to catalyze the Mg 2؉ -dependent conversion of farnesyl diphosphate to the sesquiter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
150
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(153 citation statements)
references
References 30 publications
3
150
0
Order By: Relevance
“…1A). Terpene synthases with similar functions sometimes group in the same clusters, as illustrated by epi-isozizaene synthases (cluster 4), 2-methylisoborneol synthases (cluster 7), aristolochene synthases (cluster 13), and geosmin synthases (cluster 8) (27)(28)(29)(30). (See Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A). Terpene synthases with similar functions sometimes group in the same clusters, as illustrated by epi-isozizaene synthases (cluster 4), 2-methylisoborneol synthases (cluster 7), aristolochene synthases (cluster 13), and geosmin synthases (cluster 8) (27)(28)(29)(30). (See Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3). In contrast to these eukaryotic isoprenoid cyclases, only limited studies on prokaryotic isoprenoid cyclases have been reported so far [10,62]. Therefore, studies were conducted to investigate the biosynthetic genes and enzymes of isoprenoid antibiotics produced by actinomycetes, particularly focusing on the cloning and characterization of the genes of the mevalonate pathway and the genes of isoprenoid cyclase.…”
Section: Biosynthesis Of Isoprenoidsmentioning
confidence: 99%
“…Dr Rory Watt (now at the University of Hong Kong) then expressed the Cyc2 protein and established that it catalyzed cyclization of FPP to the monocyclic sesquiterpene alcohol (4S,7R)-germacradienol (17), an activity that he also showed was due exclusively to the N-terminal half of the protein (Figure 12). 92 This discovery, however interesting, might have remained only a curiosity, had not Keith Chater, Greg Challis and their collaborators at the John Innes, using their newly developed method for generating directed in-frame gene knockouts in Streptomyces, discovered simultaneously that the same 2.3-kb gene is essential to the biosynthesis of the well-known odoriferous compound geosmin (18), a volatile degraded sesquiterpene produced by all Streptomyces that is responsible for the universally recognized odor of moist soil. 93 Two graduate students in Editorial my laboratory, Xiaofei He (now at Shanghai Jiaotong University) and Jiaoyang Jiang (now an Assistant Professor at the School of Pharmacy at the University of Wisconsin), then made the unexpected discovery that germacradienol synthase is in fact a bifunctional geosmin synthase enzyme that converts FPP all the way to geosmin, with the C-terminal domain catalyzing an unprecedented cyclization-fragmentation of the initially formed germacradienol (Figure 12).…”
Section: Enzymology and Molecular Genetics Of Natural Product Biosyntmentioning
confidence: 99%